Voltammetric behavior of benznidazole at a DNA-electrochemical biosensor - La-Scalea, M. A. (2002)
Benznidazole is a drug used commonly as a therapeutic agent against Chagas' disease in Brazil. To clarify the cytotoxic action of benznidazole the electrochemical reduction of benznidazole has been investigated using a DNA-electrochemical biosensor, prepared by modification of a glassy carbon electrode with DNA, and the results compared with reduction at a bare glassy carbon electrode. The dependence of peak potential with pH follows slopes of 59 and 52 mV per pH unit in acid media, respectively, which corresponds to a mechanism involving the same number of electrons and protons. In neutral and alkaline solution no significant dependence of peak potential with pH was found. During the electrochemical reduction of benznidazole the formation of the hydroxylamine derivative occurs, involving a total of four electrons. The potentials for reduction were less negative when using the DNA-modified glassy carbon electrode than at the bare glassy carbon electrode although the mechanism was the same, and at pH 7.51 the peak current was four times higher than that obtained with the bare electrode. The DNA-biosensor enabled pre-concentration of the drug onto the electrode surface and the in situ damage caused to the DNA on the electrode surface by the product of benznidazole reduction could be detected electrochemically. The results are in agreement with the hypothesis that the hydroxylamine derivative is the reactive species responsible for the cytotoxic action of benznidazole.